2012
DOI: 10.4028/www.scientific.net/amr.549.152
|View full text |Cite
|
Sign up to set email alerts
|

Study of Effect of Water on the Physicochemical Properties of 1-Buthyl-3-Methylimidazolium Chloride Ionic Liquids

Abstract: The density, viscosity, conductivity and the electrochemical window of 1-buthyl-3-methyl- imidazolium Chloride ionic liquids([Bmim]Cl) and its water mixture have been determined at 298.15 K and atmospheric pressure. It was found that the density and conductivity of [Bmim]Cl/water, increase with the increase the water concentration at the same temperature, whereas the viscosity and electrochemical windows of [Bmim]Cl/water decrease. The viscosity of pure ionic liquids decreases with the increase of the temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Bose et al 17 reported that solution viscosity, which controls diffusivity of reactant and catalyst, plays an important role in the enzymatic hydrolysis of cellulose. The higher viscosity of the [Bmim][Cl]-containing aqueous solution 16 than water should be partly responsible for the decreased activity of cellulase observed in both liposomal and free enzyme systems. In Figure 2B, the hydrolysis reaction in the liposomal system monotonically progresses even in the later stage of the reaction in contrast to the case of free cellulase-catalyzed reaction.…”
Section: Effect Of Liposome Membrane On Enzymatic Hydrolysis Of Insolmentioning
confidence: 99%
See 1 more Smart Citation
“…Bose et al 17 reported that solution viscosity, which controls diffusivity of reactant and catalyst, plays an important role in the enzymatic hydrolysis of cellulose. The higher viscosity of the [Bmim][Cl]-containing aqueous solution 16 than water should be partly responsible for the decreased activity of cellulase observed in both liposomal and free enzyme systems. In Figure 2B, the hydrolysis reaction in the liposomal system monotonically progresses even in the later stage of the reaction in contrast to the case of free cellulase-catalyzed reaction.…”
Section: Effect Of Liposome Membrane On Enzymatic Hydrolysis Of Insolmentioning
confidence: 99%
“…For example, it has been reported that 1-butyl-3-methylimidazolium chloride ([Bmim][Cl]) can effectively dissolve insoluble cellulose. 5,[10][11][12][13] ILs were reported to cause the deactivation of cellulase through direct interaction to the enzyme molecules 14,15 and increasing solution viscosity 16 which limits diffusivity of the catalysts and reactants. 17 Removal of IL from cellulose pretreated with the IL is cumbersome and sometimes not cost effective.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, LTCT also contains some water. The existence of water has a great influence on the physical properties of ILs, such as density and viscosity. , More importantly, the existence of water can affect the extraction efficiency of ILs for phenolic compounds. Ren et al reported that the extraction efficiency of choline chloride (ChCl) decreased from 92.4 to 83.8% when the water content of model oil increased from 1 to 7% .…”
Section: Introductionmentioning
confidence: 99%
“…There are a large number of experimental studies have been performed with the aim of studying thermodynamic and dynamic properties of mixtures of imidazolium-based ILs with alcohols, such as densities and excess molar volumes, refractive indices, conductivities, and viscosities [12][13][14][15]. For computational studies, some efforts have been dedicated over the past years to investigate the thermodynamic and structural properties of both pure ILs and of IL/solvent mixtures [16][17][18][19][20][21][22].However, a systematic study of the relation between the structure and the properties of the mixture is not available at this point. A detailed knowledge and understanding of the physicochemical properties of alcohol/IL mixtures is of fundamental importance to further explore the large number of potential academic and industrial applications of ILs.…”
Section: Introductionmentioning
confidence: 99%